OPTIMALISASI FUNGSI MUSHOLA MELALUI PARTISIPASI MASYARAKAT: IMPLEMENTASI PROGRAM KEBERSIHAN DAN EDUKASI DI DESA DUSONYO, THAILAND - Mohammad Khoridatul Huda; Zulkarnain, Siti Aimmatuz; Khasanah, Uswatul; Halim, Mochammad Mey Lano Novardy; Budianto, Kharis (FIP UNIRA MALANG, 2025)
This community service project aimed to optimize the function of the mushola (prayer room) in Dusonyo Village, Chanae District, Narathiwat, Thailand, by transforming it into a clean, comfortable, and functional worship space. The program employed a Participatory Action Research (PAR) approach, engaging the local community in cleaning, revitalization, and reactivation of the prayer room as both a spiritual and social center. Activities were carried out regularly on Saturdays and Sundays from 9 February to 8 March 2025. The results indicate an increased utilization of the prayer room for religious activities such as congregational prayers, Qur’an recitations (tadarrus), and Islamic study sessions. The program's success was driven by active community participation, support from local leaders, and collaboration with the takmir (prayer room administrators). Language barriers were effectively mitigated through participatory social engagement. This initiative is recommended as a model for similar programs in other regions, emphasizing sustainability and cross-sectoral involvement.